Variáveis reprodutivas do Surubim do Iguacu (Steindachneridion melanodermatum) e comparação do desenvolvimento do ontogenetico com o jundiá (Rhamdia quelen) - Sant´anna, João Felipe Moutinho (2009)
Species of large size and commercial value are found in the basin of the Iguaçu, with the highlights, representatives of the order Siluriformes. The genus Steindachneridion belongs to the order Siluriformes and has restricted distribution of some rivers basins of South America. The endemic Iguaçu’s surubim (Steindachneridion melanodermatum) as well as other catfish, has characteristics that have attracted great interest for cultivation. Another representative of Siluriformes, with broad representation in the Iguaçu river, the jundiá (Rhamdia quelen), this species has already successfully introduced in commercial farming. The purpose of this study was to investigate the reproductive processes in the laboratory in order to define better strategies for induced spawning, fertilization rate and embryo-larval development of Siluriformes. The experiment was conducted in fishponds Station studied ichthyology Plant Ney Braga, located in the reservoir of Salto Segredo, PR. In order to evaluate qualitative and quantitative characteristics of semen surubim, S. melanodermatum, used the eleven males weighing between 1.1 and 2.4 kg were subjected to treatment hypophysation. The volume of semen collected from 0.4 to 2.5 mL. Sperm motility after collection has remained between 85 to 292 seconds when activated with water tank, and 66 and 268 seconds when activated with distilled water. For sperm concentration, we found values that ranged between 28 and 88 x106 sperm / mm ³. From 0 to 74 hours after fertilization, were performed on 37 samples every two hours for each species. Was observed organogenesis, hatching with closed mouth and anus, formation of the heart, eyes, fins and digestive tract. The larvae of S. melanodermatum and R. quelen have similar characteristics during development.